Fate of Antioxidants in Gut and Interaction of Gut Metabolites and Gut Microbiota - Xu, Baojun (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It is widely accepted that antioxidants can help in disease prevention by effectively quenching free radicals or inhibiting damage caused by oxidative stress. However, the final fate of antioxidants in the gut, how antioxidant metabolites affect gut microbiota, and how gut microbiota affect the metabolism of antioxidants are not fully understood. This Special Issue collected the latest research findings and review articles, bringing together current research and critical thinking on the fate of phytochemical antioxidants in the gut and the role antioxidant gut metabolites play in reducing oxidative stress in various gut and metabolic diseases. Both in vitro and in vivo studies relating to any of the following topics will be considered: fate of antioxidants in the gut; antioxidative activities of phytochemicals in the digestive system; molecular mechanisms of phytochemical antioxidants in maintaining gut health; and interactions of antioxidant metabolites and gut microbiota.